Social Criticism in Bintang Emon's Stand-Up Comedy Video "Corruption Is Not Just an Act of Theft" - Yuyun Yunengsih; Desty Endrawati Subroto; Mahpudoh Mahpudoh (EDUJAVARE: International Journal of Educational Research, 2026)
The video raises the issue of corruption as a social problem that has a wide impact on society and is conveyed through a comedic style that contains satire on the reality of law enforcement in Indonesia. This study aims to analyze social criticism in the Bintang Emon stand-up comedy video with the theme of corruption on Instagram using Teun A. van Dijk's Critical Discourse Analysis. This study uses a qualitative approach with a descriptive method. The research data was in the form of speech in one Bintang Emon stand-up comedy video with the theme of corruption uploaded on @bintangemon's Instagram account. Data was obtained through the technique of watching and recording by observing the content of the video, then analyzed using the Teun A. van Dijk Critical Discourse Analysis model which includes macro structures, superstructures, microstructures, social cognition, and social context. The validity of the data was tested using the theory triangulation technique by comparing the results of the analysis based on the concept of Critical Discourse Analysis by Teun A. van Dijk and the theory of social criticism. The results of the study showed that the video contained social criticism of corrupt practices which were described as a form of state erosion that benefited a few people and harmed the wider community. In the macro structure, the main theme was found in the form of the importance of eradicating corruption. In the superstructure, the discourse is arranged through opening, development, and closing that builds a humorous effect as well as sarcasm. In the microstructure, the use of diction, sentence forms, and language styles strengthens the message of social criticism.